Implementation of Solok Selatan Regency Regional Regulation No. 1 of 2020 concerning Public Order and Peace of Mind - Aulia, Ulfita; Daipon, Dahyul (Yayasan Lembaga Studi Makwa, 2024)
The habit of the people of Nagari Padang Air Dingin to dry rice on the main road was the primary motivation for this research. This practice is clearly not in accordance with Article 9, Paragraph 1, letter h of South Solok Regency Regional Regulation No. 1 of 2020 concerning Public Peace and Order, and it has several negative impacts. These impacts include a reduction in the area's aesthetic appeal, roads becoming dirty due to rice residue, main roads becoming slippery, and traffic jams that disrupt public transportation. This research employs a normative-empirical legal methodology, collecting primary data from interviews with informants. The findings indicate that although South Solok Regency Regional Regulation No. 1 of 2020, particularly the section on the prohibition of drying agricultural products on the highway, has been implemented more effectively compared to previous years, there are still areas where enforcement remains less than optimal. Factors such as environmental conditions continue to pose challenges to achieving full compliance. Furthermore, this regulation aligns with the concept of siyasah tanfidziyah (administrative policy), as in Islamic jurisprudence, the main goal is to achieve public benefit and prevent harm. Thus, the enforcement of Article 9, Paragraph 1, letter h of Regional Regulation No. 1 of 2020 contributes to protecting individuals from potential accidents or conflicts within the community.